DAMPAK PENGGUNAAN GADGET PADA ANAK USIA DINI - Hikmaturrahmah, Hikmaturrahmah (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
The 2003 National Education System Law which describes the time of children is 0-6 years of age) and some child education experts provide limitations of 0-8 years. At this time, Children who are in a time of curiosity are very helpful to read and use gadgets and some of the applications in them. With the development of information technology, children today are calling for far more